Evaluation of productive parameters in guinea pigs raised at high density during growth and fattening - Livia-Tacza, Mayra Alejandra (2026)
Introduction. The rearing of guinea pigs (Cavia porcellus) is key to the food supply and economy of Andean countries such as Peru. However, their productivity may be affected by inadequate management, particularly stocking density, whose impact has not yet been fully evaluated. Objective. To evaluate the productive efficiency of guinea pigs subjected to high stocking densities. Materials and methods. The experiment was conducted at the Small Animals Laboratory of the National Agrarian University La Molina (UNALM), in Lima, Peru, over eight weeks (January to March 2022). A total of ninety improved male guinea pigs of the Cieneguilla-UNALM genotype were used, with an average initial weight of 338.57 g (15 ± 3 days of age). The experimental design was completely randomized, with three treatments: 0.10 m²/animal (T1), 0.066 m²/animal (T2), and 0.050 m²/animal (T3), with three replicates of ten guinea pigs each. The animals were fed ad libitum with balanced feed and forage, and had continuous access to water. The evaluated productive variables were initial and final weight, weight gain, feed intake (daily, weekly, and total), feed conversion ratio, mortality, carcass lesions, visible fat scoring, and carcass yield. Results. Treatment T1 showed the highest weight gain and total feed intake, while T3 exhibited the best feed conversion ratio and the lowest mortality. Carcass yield and visible fat content were higher in T1; however, T3 showed fewer signs of carcass lesions (p < 0.05). Conclusions. Stocking density in guinea pigs did not significantly affect the evaluated parameters. However, the highest density (T3) reduced the incidence of lesions, indicating less competitive behavior among the animals.